Intrascleral Suture Anchoring: A Flapless/Grooveless Four-Point Intraocular Lens Fixation Technique - Hu, Xin (J Ophthalmol, 2020)
PURPOSE: We describe a minimally invasive suture fixation technique for four-point fixation of intraocular lenses (IOLs) in the treatment of aphakic eyes, namely, the intrascleral suture anchoring technique. Neither scleral flaps nor large conjunctival dissections are required. METHODS: This study included 11 eyes (11 patients). After looping the eyelets on the IOL haptics and externalizing the threads, the curved needle attached to the externalized thread was started with two sequential intrascleral passes from the first fixation point to reach the second fixation point. The same procedure was performed for the other side of the IOL. A fixation knot was created in the sclerotomy by the two ends of the thread to close the suture loop for IOL fixation. Another knot was created about 2 to 3 mm from the exiting point and was intrasclerally anchored by the aid of the attached curved needle. RESULTS: The mean postoperative follow-up period was 9.7 ± 5.8 months (range 5–15 months). The IOLs of all eyes remained well positioned and stable postoperatively. The postoperative visual acuities were improved. No suture erosion, suture loosening, hypotony, scleral atrophy, chronic inflammation, retinal tear, and/or detachment were observed within the follow-up period. CONCLUSION: The present technique is an alternative, flapless method for the four-point suture fixation of IOLs. It provides both minimal surgical trauma and reliable stability.